Characterization of European cities’ climate shift – an exploratory study based on climate analogues - Goyette, S. (2020)
This paper aims to use climate analogues to characterize the climate shift of cities and to explore its implications as well as potential applications of this approach. The authors propose a methodology to match the current climate of cities with the future climate of other locations and to characterize cities’ climate shift velocity. Employing a sample of 90 European cities, the authors demonstrate the applicability of this method and characterize their climate shift from 1951 to 2100. Results show that cities’ climate shift follows rather strictly north-to-south transects over the European continent and that the average southward velocity is expected to double throughout the twentyfirst century. These rapid shifts will have direct implications for urban infrastructure, risk management and public health services.